Therapy of IBS: Is a Low FODMAP Diet the Answer? - Manning, Lauren P.; Yao, C. K.; Biesiekierski, Jessica R. (Frontiers in Psychiatry, 2020)
Irritable bowel syndrome (IBS) is the most prevalent functional gastrointestinal disorder with a worldwide prevalence of 11%. It is characterized by abdominal pain and altered bowel habits in the absence of underlying unique pathology. The condition is associated with poor quality of life and high use of healthcare resources required for management. The low FODMAP diet (LFD) is a recognized treatment for symptom management of IBS; however, approximately 30% of patients do not respond. The aim of this review was to understand the effectiveness and application of the LFD compared with other dietary and non-dietary interventions. Ten studies were included, eight of which assessed the LFD against other dietary interventions including traditional dietary advice, modified National Institute for Health and Care Excellence guidelines, a high FODMAP diet, gluten-free diet and Mediterranean diet, generalized dietary advice, probiotics, and a sham diet. Two studies compared a LFD to non-diet interventions of gut directed hypnotherapy or yoga. The findings clearly support the LFD as an effective treatment in IBS, and although it highlights the role for microbiota and current psychosocial state, it remains challenging to identify what combination of treatments may be best to ensure a personalized approach and overall higher response rates to IBS therapy.